A CRITICAL DISCOURSE ANALYSIS OF KING SALMAN’S SPEECH AT THE G20 RIYADH SUMMIT - Zumrotul Imanda Wachid Hakim; Mohammad Pribadi; Nabilla Rana Dermawan (Adabiyyāt: Jurnal Bahasa dan Sastra, 2025)
This study examines the discourse strategies employed by King Salman bin Abdulaziz Al-Saud in his speech at the 2020 G20 Riyadh Summit using Teun A. van Dijk’s Critical Discourse Analysis (CDA) framework. It aims to reveal how the ideology of monarchical legitimacy is constructed through textual structures at the macro-, super-, and microstructural levels, and how these constructions shape social cognition and reproduce power relations within the global socio-political context. The significance of this study lies in its effort to understand political speeches delivered at international forums as symbolic instruments of legitimation, particularly those produced by monarchical leaders. The findings indicate that King Salman’s speech strategically constructs a representation of Saudi Arabia as a responsible, solution-oriented, and humanitarian-oriented global actor. This discourse frames G20 countries as legitimate authorities in determining the direction of global governance, while positioning the international community as beneficiaries of these policies. These findings demonstrate that G20 discourse functions as a discursive mechanism to normalize and legitimize Saudi Arabia’s monarchical leadership within a global political landscape marked by uncertainty resulting from health, economic, and global governance crises.